Demographic influences on knowledge management awareness: A case study of a Philippine state university - Homillano, Myra Luz M.; Petil, Rochell R.; Homillano, Ludivico B. (Edelweiss Applied Science and Technology, 2025)
Examining the demographic influences on knowledge management (KM) awareness among personnel at Central Bicol State University of Agriculture (CBSUA), Philippines, addresses a critical gap in understanding KM implementation. The data were collected from 123 participants (71 faculty, 52 non-teaching staff) using stratified purposive sampling through a validated survey instrument (Cronbach's α = 0.85). To analyze KM awareness across demographic variables, the Mann-Whitney U and Kruskal-Wallis tests were used. The median (4.000) KM awareness score was uniformly moderate-to-high across all groups. The analysis revealed that younger employees (25-35 and 36-46 years) demonstrated higher awareness levels (Z = 1.14 and 1.03, respectively) than older employees (Z = -1.22 to -1.32). The 6-10 years of experience group had the highest KM awareness (Z = 1.78), while the 30+ years of experience group showed the lowest awareness (Z = -2.04). No significant differences emerged by gender (p = 0.0851), age (p = 0.181), education (p = 0.202), or experience (p = 0.101). The findings provide a basis for developing KM strategies tailored to specific demographic profiles among teaching and non-teaching personnel, enabling the institution to transform tacit knowledge into explicit organizational assets that will improve academic quality and administrative efficiency.